CD34 and CD117 Stemness of Lineage-Negative Cells Reverses Memory Loss Induced by Amyloid Beta in Mouse Model - Bali, Parul; Bammidi, Sridhar; Banik, Avijit; Nehru, Bimla; Anand, Akshay (Frontiers in Behavioral Neuroscience, 2018)
Majority of the neurodegenerative disorders including Alzhe3imer’s disease (AD) are untreatable and which occur primarily due to ageing and rapidly changing lifestyles. The rodent AD models are critical for investigating underlying disease pathology and also to evaluate novel therapeutic targets in preclinical settings. We aimed to characterize the stemness properties of human umbilical cord blood (hUCB) derived lineage negative stem cells (lin-ve) based on CD34 and CD117 expression as well as surface morphology using flow Cytometry and SEM, respectively. Furthermore, its efficacy by transplantation in varying dose of amyloid β-42 hippocampal injury in mouse model was tested. The hUCB lin-ve stem cells reversed the memory loss more effectively at micromolar concentration Aβ-42 induced injury and not picomolar concentration. More studies are required to delineate the underlying molecular events associated with hUCB lin-ve stem cells.